Experimental Research on Automatic Alignment and Control Algorithm of Spatial Light-Fiber Coupling - Ke, Xizheng; Yin, Benkang (International Journal of Optics, 2021)
This study aims to solve the difficulties in the coupling between space light and single-mode fiber (SMF) in free-space optical communication. A fiber coupler based on two-dimensional (2D) piezoelectric ceramics was developed, which uses the stochastic parallel gradient descent (SPGD) algorithm to realize the automatic coupling of space light-SMF. In addition, a spatial light-SMF alignment experimentation platform was built indoors to verify the effectiveness and practicality of the 2D piezoelectric ceramic fiber coupler. The results show that the use of the SPGD algorithm can realize the automatic alignment of fiber position coupling, and the SMF coupling efficiency reaches 52.58% when the system is closed loop. 2D piezoelectric ceramic fiber couplers have unique advantages of low cost, simplified structure, and easy array expansion and can effectively solve the difficulty in the alignment of spatial light-SMF coupling. This study will serve as a significant reference for the research on spatial fiber-coupled array technology.